Research on Possible Effects of Acrylamide and Vitamin E Administered to Pregnant Rats on Placenta Tissue - Mehmet Erman Erdemli; Eyüp Altınöz; Zeynep Aksungur; Zümrüt Doğan; Harika Gözükara Bağ; Yusuf Türköz (Turkish Journal of Agriculture: Food Science and Technology)
Investigate the changes that occur in the placenta tissues of pregnant rats that were administered acrylamide (AA) and vitamin E as a protective agent during pregnancy. Thirty rats that were proven positive for pregnancy with vaginal smear test were randomly distributed into control, corn oil, vitamin E, acrylamide and vitamin E + acrylamide groups. Pregnant rats were decapitated on the 20th day of the experiment. Malondialdehyde (MDA), reduced glutathione (GSH), total antioxidant capacity (TAS), total oxidant capacity (TOS) and Xanthine oxidase (XO) levels were measured in placenta tissues. It was determined that acrylamide application during pregnancy statistically significantly increased MDA, TOS and XO levels and reduced GSH and TAS levels in the placenta tissue of pregnant rats when compared to all other groups, and GAS and TAS levels statistically significantly increased in vitamin E administered group when compared to all other groups and TOS and XO levels were decreased to control group levels. It was observed that orally administered AA changed the antioxidant / oxidant equilibrium favoring the oxidants by increasing MDA, XO and TOS levels in pregnant rats and caused oxidative stress, while vitamin E administration returned the antioxidant / oxidant equilibrium back to normal levels, preventing oxidative stress induced toxicity.